2022
DOI: 10.1039/d1nj05162h
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic oxidation-functionalization of the aryl moiety in van Koten's pincer complex (NCN)Ni(ii)Br: relevance to carbon–heteroatom coupling reactions promoted by high-valent nickel species

Abstract: The growing popularity of metal-promoted C-H functionalization methodologies has led to increased efforts aimed at improving our understanding of the mechanistic underpinnings of C-C or C-heteroatom bond forming steps. One...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…For example nickel-alkoxides are demonstrated to be intermediates in coupling processes (via ligand exchange or β-H abstraction, Scheme 3, top). [23,[41][42][43][44][45][46] Furthermore, insertion in NiÀ O bonds of CO 2 , CO, nitriles, ketones, isocyanate (Scheme 3, bottom); [35,36,38,39] has been established for neutral mono-alkoxide nickel complexes; as well as [OR] À ligand exchange [33] and formal reductive elimination at Ni. [37] During these studies, and as mentioned by Krossing et al, we observed that PhF!Al(OR F ) 3 adduct suffers from poor thermal stability liberating the Al(OR F ) 3 Lewis acid at room temperature, that evolves via abstraction of one of its own fluorine to form the [(R F O) 2 Al(μ-F)] 3 ring 2 (see below, Scheme 4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example nickel-alkoxides are demonstrated to be intermediates in coupling processes (via ligand exchange or β-H abstraction, Scheme 3, top). [23,[41][42][43][44][45][46] Furthermore, insertion in NiÀ O bonds of CO 2 , CO, nitriles, ketones, isocyanate (Scheme 3, bottom); [35,36,38,39] has been established for neutral mono-alkoxide nickel complexes; as well as [OR] À ligand exchange [33] and formal reductive elimination at Ni. [37] During these studies, and as mentioned by Krossing et al, we observed that PhF!Al(OR F ) 3 adduct suffers from poor thermal stability liberating the Al(OR F ) 3 Lewis acid at room temperature, that evolves via abstraction of one of its own fluorine to form the [(R F O) 2 Al(μ-F)] 3 ring 2 (see below, Scheme 4).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from these scattered examples, complexes featuring Ni−O bonds are quite reactive. For example nickel‐alkoxides are demonstrated to be intermediates in coupling processes (via ligand exchange or β‐H abstraction, Scheme 3, top) [23,41–46] . Furthermore, insertion in Ni−O bonds of CO 2 , CO, nitriles, ketones, isocyanate (Scheme 3, bottom); [35,36,38,39] has been established for neutral mono‐alkoxide nickel complexes; as well as [OR] − ligand exchange [33] and formal reductive elimination at Ni.…”
Section: Introductionmentioning
confidence: 99%